The Effects of Using Karaoke Videotape of Nursing Care for Chronic Kidney Disease Patients on Knowledge of Nursing Students, Faculty of Nursing, Prince of Songkla University - ยอดไชย, กันตพร; มานะสรุการ, จารุวรรณ; กฤตย์ปรีชา, จารุวรรณ (วารสารพยาบาลศาสตร์และสุขภาพ, 2012)
The purposes of this pre-test/-post-test quasi-experimental study were to examine differences ofknowledge between nursing students who attendedtraditional class (control group) and those  who attendedtraditional class plus karaoke videotape lesson(experiment group)  and to examine studentûs satisfactionfor the karaoke videotape lesson. Matching of grade-point average (GPA) of 60 second-year nursingstudents was conducted. There were 30 students in eachgroup. Instruments used in this study included1) karaoke videotape of nursing care for chronic kidneydisease patients, 2) pre-test/-post-test for the lessonsdifficulty range: p = 0.25-0.88, discrimination power range: r = 0.47-0.75, correctness: 0.79 (using Kuder-Richardson 20 analysis), and 3) satisfaction of usingkaraoke videotape questionnaire. The content validityof the questionnaire was approved by 5 experts andalpha coefficient of the questionnaire was 0.83. Datawere analyzed using percentage, standard deviation,paired t-test, and t-test.The effectiveness of using karaoke videotape inthis study was 84.70/96 (with expected value of 80/80). The mean score of students knowledge level afterstudying with the videotape was significantly higherthan before the study at (x= 12.40, S.D. = 2.22)compare with (x= 8.47, S.D. = 2.26) at 0.001. Thescore for students who received attended traditional classplus karaoke videotape lesson was significantly higherthan students who received only attended traditionalclass at (x= 12.40, S.D. = 2.22) compare with(x= 7.60, S.D. = 4.30) at 0.001. The level ofsatisfaction of nursing students for the karaoke videotapelesson was high to highest. Reasons given by thosewith the highest satisfaction level were that the lessonis good for self-study (73.30%) encourage moreknowledge seeking (70%) and motivate the learningprocess (63.40%).The indications are that karaoke videotape isuseful for enhancing the teaching and learning processin nursing science and it can effectively encourageself-directed learning for nursing students.